2013
DOI: 10.1002/smll.201203178
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Partially Aligned Semiconductive Single‐Walled Carbon Nanotube Transistors Achieved with a Parallel Technique

Abstract: Single-walled carbon nanotubes (SWNTs) are widely thought to be a strong contender for next-generation printed electronic transistor materials. However, large-scale solution-based parallel assembly of SWNTs to obtain high-performance transistor devices is challenging. SWNTs have anisotropic properties and, although partial alignment of the nanotubes has been theoretically predicted to achieve optimum transistor device performance, thus far no parallel solution-based technique can achieve this. Herein a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…However, due to an inefficient growth-control over CNT chirality in this way, metallic (m-) SWCNTs, to some extent, are always present in devices, significantly suppressing device performance. Comparatively, solution-based post-assembly methods, such as shear-force guided SWCNT alignment [23,24] is known to lack fine-control over CNT orientations and locations. The Langmuir-Schaefer method [25,26], a widely used technique for fabricating molecular thin films, illustrates inefficiency in assembling monolayer SWCNT arrays, thus detrimental to transistor performances because of the increased inter-tube electrostatic screening effect in multilayer assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to an inefficient growth-control over CNT chirality in this way, metallic (m-) SWCNTs, to some extent, are always present in devices, significantly suppressing device performance. Comparatively, solution-based post-assembly methods, such as shear-force guided SWCNT alignment [23,24] is known to lack fine-control over CNT orientations and locations. The Langmuir-Schaefer method [25,26], a widely used technique for fabricating molecular thin films, illustrates inefficiency in assembling monolayer SWCNT arrays, thus detrimental to transistor performances because of the increased inter-tube electrostatic screening effect in multilayer assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding have implications in the field of anisotropic conduction which is of great scientific and technological interest. Aligned SWNTs have been used as the building blocks of high performance transistors [33][34][35][36][37] , light-emitting diodes, 38 logic gates, 39 radio-frequency devices, 40 transparent conductive films, 41 sensors, 42,43 , photodetectors and photoswitches 44 and synaptic transistors. 45 The ability to modulate the transport properties of aligned SWNTs in a controlled manner offers a route to expand the functionality of these technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of polymer/CNTs composite, it is found that the CNTs tend to align 45° from the radial direction and independent of radial position and spin rate . The reported degree of alignment of the CNTs for the rotary spin method is half‐maximum‐full‐width (HMFW) of around <15° . This method is simple and robust; however, it has several limitations such as poor alignment at the center region and no control over the direction of alignment.…”
Section: Mechanisms Of Cnts Alignmentmentioning
confidence: 99%